1997
DOI: 10.1117/1.601379
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-insensitive and strain-insensitive long-period grating sensors for smart structures

Abstract: We demonstrate that temperature-and strain-insensitive long-period gratings can be fabricated in conventional optical fibers. The former is employed to measure strain with resolution of 20 ⑀ under thermal fluctuations in the surroundings, while the latter is used to detect temperature variations as small as 0.8°C in the presence of axial strain. © 1997 Society of Photo-Optical Instrumentation Engineers. [S0091-3286(97)00407-8]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
63
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(67 citation statements)
references
References 3 publications
(8 reference statements)
0
63
0
1
Order By: Relevance
“…For Λ < 100 μm both contributions to the strain sensitivity are negative. 20,48 For example, Bhatia et al have demonstrated strain sensitivity for LPGs of 0.04 pm∕με and −2.2 pm∕με with different grating periods. 48 Selecting an appropriate periodicity and fiber composition for LPGs gives the possibility of designing the sensor strain-sensitive or insensitive, if the material and waveguide contributions are equal but with opposite sign.…”
Section: Long-period Strain Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…For Λ < 100 μm both contributions to the strain sensitivity are negative. 20,48 For example, Bhatia et al have demonstrated strain sensitivity for LPGs of 0.04 pm∕με and −2.2 pm∕με with different grating periods. 48 Selecting an appropriate periodicity and fiber composition for LPGs gives the possibility of designing the sensor strain-sensitive or insensitive, if the material and waveguide contributions are equal but with opposite sign.…”
Section: Long-period Strain Sensitivitymentioning
confidence: 99%
“…20,48 For example, Bhatia et al have demonstrated strain sensitivity for LPGs of 0.04 pm∕με and −2.2 pm∕με with different grating periods. 48 Selecting an appropriate periodicity and fiber composition for LPGs gives the possibility of designing the sensor strain-sensitive or insensitive, if the material and waveguide contributions are equal but with opposite sign. LPGs can measure strain and temperature with an optical spectral sensitivity almost an order-of-magnitude higher than FBGs, 42 giving the possibility of utilizing it as strain or temperature sensor.…”
Section: Long-period Strain Sensitivitymentioning
confidence: 99%
“…2 Over the past few years, the LPG has also found numerous applications in the field of sensing through its sensitivities to strain, bending and shape, temperature, and the refractive index of the surrounding medium. [3][4][5][6][7] The LPG sensitivity can manifest itself in two ways; first through the spectral shift in the attenuation band, which we refer to here as spectral sensitivity, and second through a change in the strength of the attenuation band, which we refer to as a spectral profile variation.…”
Section: Introductionmentioning
confidence: 99%
“…LPG is a type of fiber device that couples light between the fundamental core mode and forwardpropagating cladding modes. This coupling results in a transmission spectrum consisting of a series of attenuation bands at distinct wavelengths [6] . These attenuation bands are sensitive to temperature, strain [6] , bending curvature [7] , and the refractive index (RI) of the surrounding material [8] .…”
mentioning
confidence: 99%
“…This coupling results in a transmission spectrum consisting of a series of attenuation bands at distinct wavelengths [6] . These attenuation bands are sensitive to temperature, strain [6] , bending curvature [7] , and the refractive index (RI) of the surrounding material [8] . The purpose of LPG-based sensors is to measure the wavelength shift of a specific attenuation band while one of the external physical parameters (i.e., temperature, strain, bend, and RI) is changing.…”
mentioning
confidence: 99%